2021
DOI: 10.2196/21244
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Access and Implications for Digital Health Interventions Among Adolescents and Young Adults in Zimbabwe: Cross-Sectional Survey

Abstract: Background Mobile phones may help young people (YP) access health information and support health service engagement. However, in low-income settings there is limited knowledge on YP’s phone and internet access to inform the feasibility of implementing digital health interventions. Objective We investigated access to information and communication technologies among adolescents and young adults in Zimbabwe. Methods A cross-sectional population-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…Our findings are consistent with studies conducted between 2014 and 2020 in other parts of SSA. A 2018 study among youth age 13-24 years in Zimbabwe reported 67% phone access, 57% smartphone access, and higher phone and internet access among older, more highly educated, and male youth (24). A 2014-2016 study among youth aged 18-24 years living with HIV in Uganda reported 94% owned a phone and 37% owned a smartphone, with higher internet use among older youth and men (25).…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Our findings are consistent with studies conducted between 2014 and 2020 in other parts of SSA. A 2018 study among youth age 13-24 years in Zimbabwe reported 67% phone access, 57% smartphone access, and higher phone and internet access among older, more highly educated, and male youth (24). A 2014-2016 study among youth aged 18-24 years living with HIV in Uganda reported 94% owned a phone and 37% owned a smartphone, with higher internet use among older youth and men (25).…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Recent research has suggested that mobile phone interventions may be feasible among young people in Zimbabwe but have the potential to increase inequities if internet access is a prerequisite for intervention receipt [ 12 ]. The current study was in line with this finding, with young people favouring a non-internet dependent intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Girls aged 15-19 have relatively low awareness of EC compared to young women aged 20-24 in all countries studied. The differences could be explained by better exposure of young women (aged 20-24) to information sources relative to adolescent girls [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%